HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN KEJADIAN POST PARTUM BLUES - ishak, Isnawati adeningsih; Safitri, Rani; Kartikasari, Linda (NHM PRESS, 2024)
Having a baby is a moment that is always anticipated and expected by every married couple. But sometimes this moment of happiness actually turns into a stressful condition for the mother, known as postpartum blues or baby blues syndrome. The purpose of this study was to determine whether there is a relationship between family support and the incidence of postpartum blues at the Dr. Josef Tuda Tombatu Clinic.This study is a type of analytic survey with a cross sectional design. The sampling technique used in this study was total sampling with a total of 13 postpartum mothers. Data analysis used is the sperman rank statistical test with a significance level of 5% (0.05). The results showed that 77% of postpartum mothers experienced postpartum blues, and 38% of them experienced mild postpartum blues. Of the 13 postpartum mothers, almost half, namely 46%, received less family support. The results of data analysis with the spearman rank test showed ρ value = 0.000 which means that there is a relationship between family support and postpartum blues in Klinlik dr. Josef Tuda Tomblatu. Correlation coefficient shows -0.875 which means that the relationship between family support and the incidence of postpartum blues is very strong. Translated with DeepL.com (free version)Therefore, there is a need for very good family support for postpartum mothers, because good support from the family will provide its own emotional strength for postpartum mothers.